Farmer perceptions of the relative usefulness of information providers and technology transfer methods. Issue 3 (3rd July 2017) - Corner-Thomas, R. A.; Kenyon, P. R.; Morris, S. T.; Ridler, A. L.; Hickson, R. E.; Greer, A. W.; Logan, C. M.; Blair, H. T.
ABSTRACT: In New Zealand, little is known about the preferences of sheep farmers for different information providers and technology transfer methods. A survey was undertaken to determine the usefulness of these sources of information and the influence of demographic factors such as age, education and farm size. The results of the survey indicated that preference for information providers and technology transfer methods varied widely. In addition, for the majority of information providers and technology transfer methods at least one demographic factor (education, farm size or age) influenced their perceived usefulness. The delivery of information to farmers, therefore, needs to be conducted in a targeted way using a number of different information sources and methods to ensure maximum uptake of the information. Providing information in a way that combines a number of information sources and delivery methods is likely to have the greatest impact.